Kinetic Analysis of the Oxidation of Nitrate Ion by Methylthioninium Chloride in Acid Medium - UP Ese; MD Faruruwa (Journal of Applied Sciences and Environmental Management, 2014)
The kinetic analysis of the oxidation of nitrate ion by methylthioninium chloride in acid medium was studied using large excess of the reductant. The progress of the reactions was investigated by monitoring the decrease in absorbance. The results showed a stoichiometry of 1:1, first-order dependence in both oxidant and reductant. A second order rate equation at constant temperature was obtained ©JASEM.